ANALISIS JARINGAN SOSIAL EKONOMI PETANI KRISAN DI DESA HARGOBINANGUN KECAMATAN PAKEM KABUPATEN SLEMAN - , HANIFA NOOR RAHMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed to determine economical information network of Chrysanthemum farming, costs and income structure of Chrysanthemum farming and Chrysanthemum marketing performance by calculating marketing margin, farmersâs share and marketing efficiency in Hargobinangun Village Pakem Sub-Regency Sleman Regency Yogyakarta Province. This research methodology was descriptive analytic. Data used in the research was all planting seasons data in year 2013. Sampling method of farmers was census method (saturated sampling), number of farmers that interviewed was 30 persons. Sampling method of merchants was snowball sampling wich consisted of a farmer association and 4 flower merchants (florists). Data analysis used in this research was social network analysis, farming analysis and marketing analysis. The results showed that Siswiyanto (association leader) was the most influential actor of technical cultivation, input price, output price and market target information network based on number of actors that given information (out degree centrality), the potency of being information mediator (betweeness centrality) and the easiness of information reached by all farmers (closeness centrality). Labor-source information network was separated into 6 network components because of centralizing information flows in every farmer groups. Farming analysis showed that average production-cost of Chrysanthemum farming was Rp 8.892.856 annualy